Development And Pharmacological Evaluation Of A Tamoxifen Citrate-Loaded Nanoemulsion For Targeted Breast Cancer Therapy (International Journal of Environmental Sciences, 2025)
The present study aimed to develop and optimize a tamoxifen citrate-loaded Nanoemulsion for targeted breast cancer therapy, employing a Quality-by-Design (QbD) approach. Pseudo-ternary phase diagrams were constructed using various Smix ratios (Tween 80: PEG 400), among which the 4:1 ratio demonstrated the largest Nanoemulsion region and was selected for formulation trials. A series of Nanoemulsions were prepared and characterized for droplet size, polydispersity index (PDI), zeta potential, and entrapment efficiency. Batch F6 emerged as the optimized formulation with a mean droplet size of 126.4 ± 2.8 nm, PDI of 0.234, and entrapment efficiency of 88.6 ± 1.9%. Transmission Electron Microscopy (TEM) revealed spherical, uniformly distributed, non-aggregated nanodroplets with morphology consistent with Dynamic Light Scattering (DLS) results. In vitro drug release studies showed a biphasic pattern with an initial burst followed by sustained release, achieving a cumulative release of 76.5% over 24 hours. The release kinetics best fitted the Korsmeyer–Peppas model (R² = 0.984), suggesting an anomalous, diffusion-controlled mechanism. Stability assessments confirmed the thermodynamic stability of Batch F6, with no phase separation, creaming, or significant size changes observed after centrifugation, freeze-thaw cycles, and 30-day storage at 4°C and 25°C, the optimized Nanoemulsion formulation demonstrated excellent physicochemical stability, efficient drug encapsulation, and controlled release behavior, highlighting its potential as a robust and effective carrier for targeted breast cancer therapy.